Triple S PLUS: Scaling up gender-responsive technologies for enhancing sweetpotato productivity–Ethiopia and Ghana. Project profile. - International Potato Center (International Potato Center, 2019)
By disseminating quality planting materials of improved orange-fleshed sweetpotato varieties, the International Potato Center helps farmers increase yields, enhancing household food and nutrition security and incomes. The project goes further by delivering the knowledge farmers need to maintain and multiply their planting materials, thereby building foundations for future sustainability and resilience.